Internalization of Local Cultural Values Through Ethnosport Learning in Physical Education at Elementary and Secondary Schools - Salahudin, Salahudin; Syukri, Syukri (Champions: Education Journal of Sport, Health, and Recreation, 2026)
The limited understanding of students toward local cultural values and the lack of integration of cultural elements in physical education learning have become important issues in elementary and secondary schools. This study aims to analyze the process of internalizing local cultural values through ethnosport-based learning within the context of physical education. The research employed a descriptive qualitative approach, with data collected through classroom observations, interviews with Physical Education (PJOK) teachers, and documentation studies of learning activities that utilized traditional games as learning media. The findings indicate that ethnosport-based learning is able to foster character values such as sportsmanship, cooperation, responsibility, and respect for local culture. The integration of ethnosport in physical education not only increases students’ participation in physical activities but also serves as an effective medium for instilling cultural and moral values. The implications of this study suggest that ethnosport-based physical education can become an effective learning strategy to enhance students’ active participation while strengthening cultural identity and character development, thereby supporting the implementation of the Pancasila Student Profile and the reinforcement of national character in the era of globalization.